THE FUTURE OF SCIENCE IN THE ISLAMIC WORLD (American Journal of Islam and Society, 1997)
In Islamabad, while speakers at a recent OIC/Comstech (StandingCommittee on Science and Technology) meeting titled “Science in theIslamic Polity in the Next Century” delivered tirades against the West,they conspicuously stood at a podium that boldly displayed the words“Best Western.’” This postmodern paradox captures the angst of a conferencethat called for more basic science; more and better textbooks; ascience focused on the basic human needs of food, shelter, and energy; aself-sustaining science, independent of external money or models; a “BigWestern” science that develops new laser, information, and nuclear technologies;and a science that better reflects the worldview of Islam.Amidst calls for transformation, even by individuals who had been atthe helm of the scientific establishment for the last twenty years, it wasclear that science in Muslim nations, particularly Pakistan, had gone inthe wrong direction. Even the “correct” decisions resulted in disasterbecause of science policies committed to “big science.” While nationslike Malaysia focused on products that had commercial gain or ensuredthe reduction of power of the feudal class, most Muslim nationsremained committed to self-aggrandizement and war (both imaginaryand real) with their neighbors. Instead of developing commercial scienceor local science that could meet basic needs and create better health conditionsfor women and children, nuclear strategies or “big science” wasparamount. The costs incurred by the Muslim nations are now quite evident-terrifyingly low literacy rates, the low number of high school andcollege graduates, the high number of people suffering from malnutrition,to mention but a few obvious indicators. It seems the effects ofexternal and internal colonialism remain, as do pre-Islamic dynastic battles.In the midst of the utter failure of “big science” or “western science," ...